Manufacturing of hexagonal cross-section thermoplastic matrix composite parts with automatic filament winding system - Karbuz, Pinar; Dogu, Mustafa; Ozbek, Belma (ELSEVIER SCI LTD, 2024)
Thermoplastic filament winding is a flexible manufacturing method typically used in the production of cylindrical composite structures, allowing for in-situ consolidation without the need for a second consolidation step. The objective of this study is to produce non-cylindrical geometries, typically manufactured using thermoset matrix composites according to the literature, using the thermoplastic filament winding process. For this purpose, glass fiber (GF) reinforced polypropylene (PP) prepreg tapes were used to produce hexagonal cross-section thermoplastic composite parts. The critical process parameters; hot-air heater nozzle temperature, compression roller pressure, the linear speed of mandrel rotation, and corner radius of the mandrel, were determined using the Taguchi experimental design method. The interlaminar shear strength (ILSS) and maximum compressive strength (sigma max) values were obtained as 211 MPa and 49.40 MPa as maximum, respectively. ANOVA analysis showed that the corner radius had the most significant impact on ILSS, while mandrel rotation speed and temperature were critical for sigma max.
Keywords: ANOVA; Filament winding process; Prepreg; Thermoplastic composite; TAGUCHI; TAPE; OPPORTUNITIES; IMPREGNATION; OPTIMIZATION; PERFORMANCE; TECHNOLOGY; PLACEMENT; FRICTION; DESIGN; Engineering